The Role of Planning and Communication President of the Municipal Authority to Prepare For Installation or Representative Bodies of Local Power (Study of Case in the Municipality of Liquica) - Silva, Adolfo Natalia da; Martins, Leonito M.; Cabral, Mateus X. da Costa (International Journal of Global Sustainable Research, 2024)
This research aims to investigate the role of the President of the Municipality of Liquica in planning and communication aspects, and propose solutions to challenges that may hinder his role. The qualitative research method, which includes primary and secondary data interviews and documentation, is used. The results show that while the municipality is small, authorities are ready to receive local power facilities planned by the Central Government. This policy benefits the people and promotes an integrated national development process, ensuring their well-being and the progress of the country. The research suggests that power should not be centralized solely in the Central Government, but rather, centralized in local authorities.